Upaya Dinas Perhubungan Kabupaten Siak Dalam Menertibkan Travel Ilegal Untuk Mengantisipasi Terjadinya Tindak Kejahatan (Studi Kasus Kecamatan Tualang Travel Perawang - Pekanbaru) - Alghifary, Gaizka alghifary; Neri Widya Ramailis (Sisi Lain Realita, 2024)
Transportation plays a vital role in driving economic activity and facilitating mobility in Indonesia. Among the various transportation sectors, land transport is frequently utilized in daily life and is categorized into private and public transport. Literature indicates that many private vehicles used for transport, particularly in travel services, often operate without valid route permits. This study employs a qualitative descriptive approach to gather data through observations and informants, which is then presented in a research report following the established research framework. The objective is to assess the efforts of the Siak Regency Transportation Office in regulating illegal travel services to mitigate potential criminal activities on the Perawang-Pekanbaru route. The findings reveal that, despite various initiatives, enforcement effectiveness remains limited. The Transportation Office has identified different forms of illegal travel and implemented strategies such as routine patrols, checkpoints, and cooperation with the Siak Police Department. However, challenges such as limited personnel, budget constraints, and the extensive supervision area result in the detection of only about 40% of illegal travel